The Predictive Factors of the Elderly Social Support in Tehran City, 2017 - Darvishpoor Kakhki, Ali; Gholamnejad, Hanieh (Advances in Nursing & Midwifery, 2019)
Background/objective: social support is one of the most important aspects of the life of the elderly which shows the amount of enjoying from love, help, and attention of family members, friends, and others. Therefore, the present study aims at determining the predictors of the amount of social support in the elderly of Tehran. Methods: this was a descriptive-analytic study; using cluster sampling, it was conducted on 400 elderly people visiting the parks in Tehran five districts in 2017. The personal information questionnaire and “the Canadian Community Health Survey (CCHS)-Social Support questionnaire” were used for data collection after confirming their reliability and validity. Data were analyzed using SPSS 20 software, descriptive statistics, T-test, Pearson correlation, and regression analysis. Result: the average age and the elderly social support scores were 69.1 (±7.09) and 75.33 (±20.53). The results of multiple linear regression indicated that the variables of life companions (B=3.41), marital status (B=2.47), and housing status (B=-2.87) are regarded as predicting variables of social support. Conclusion: the married elderly, those who live with their spouse and children or those owning a personal house are more socially supported than the other elderly people. The educational level and the number of children did not have a significant relationship with the amount of social support. It seems that increased support for the elderly caregivers, training specialist forces for the elderly and organizing family consultation for the elderly and their family are effective in increasing emotional support.